Respuesta :

Answer:

3n^3+4n^2+7n-14

Solution,

5n^3+4n^2-9+(-2n^3+7n-5)

= 5n^3+4n^2-9-2n^3+7n-5.

Combine the like terms,

=5n^3-2n^3+4n^2+7n-9-5

=3n^3+4n^2+7n-14

hope it helps

Good luck on your assignment

Hi1315

Answer:

[tex] = 3 {n}^{3} + 4 {n}^{2} + 7n - 14 \\ [/tex]

Step-by-step explanation:

[tex]5 {n}^{3} + 4{n}^{2} - 9 + ( - 2 {n}^{3} + 7n - 5) \\ 5 {n}^{3} + 4 {n}^{2} - 9 - 2 {n}^{3} + 7n - 5 \\ = 3 {n}^{3} + 4 {n}^{2} + 7n - 14[/tex]

hope this helps

brainliest appreciated

good luck! have a nice day!